PENGARUH KUALITAS LAYANAN, HARGA, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN KERETA API KALIGUNG DI STASIUN KERETA API TEGAL - Andri Kurniawan, 14.05.51.0142; Liana, Lie (Students' Journal of Economic and Management, 2018)
This study aims to analyze the effect of service quality, price and promotion on the satisfaction of Kaligung train customers at the Tegal train station. The object of this study is the Kaligung train customer. The population of this study is the customer of Kaligung train service users. The total population of 560 passengers is taken from the number of passengers of the Kaligung train for one departure. The number of samples used was 100 respondents. The sampling technique uses purposive sampling. Data analysis techniques used include validity test, reliability test, normality test, model test with F test, determination coefficient test (R2) and hypothesis test (t test). The results of the analysis using multiple linear regression that service quality and price variables have a positive and significant effect on customer satisfaction, while the promotion variable does not affect customer satisfaction. Based on the analysis using multiple linear regression, the variable service quality is most dominant in influencing the satisfaction of Kaligung train customers. Keywords: Quality of Service, Price and Promotion